Transforme as raízes a seguir em expoentes fracionários com base
A)
![\sqrt[3]{4}^{5} = \sqrt[3]{4}^{5} =](https://tex.z-dn.net/?f=+%5Csqrt%5B3%5D%7B4%7D%5E%7B5%7D++%3D+)
B)
![\sqrt{3}^{4} = \sqrt{3}^{4} =](https://tex.z-dn.net/?f=+%5Csqrt%7B3%7D%5E%7B4%7D++%3D+)
C)
![\sqrt[4]{2} ^{3} = \sqrt[4]{2} ^{3} =](https://tex.z-dn.net/?f=+%5Csqrt%5B4%5D%7B2%7D+%5E%7B3%7D++%3D+)
Soluções para a tarefa
Respondido por
2
Resposta:
Explicação passo-a-passo:
Respondido por
0
Explicação passo-a-passo:
Lembre-se que:
Assim:
a)
b)
c)
Perguntas interessantes
Geografia,
7 meses atrás
Português,
7 meses atrás
Matemática,
7 meses atrás
Matemática,
10 meses atrás
Biologia,
10 meses atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Geografia,
1 ano atrás